Emulsiones tipo pickering a base de almidones modificados como agentes emulsificantes. artículo de revisión (2018)
This review proposes one natural alternative to replace the conventional emulsifying agents used in cosmetic products, comparing the physicochemical properties of the different starches used in Pickering emulsions. This article elaborated three conceptual matrices that provide information of the properties that a starch must have to be chosen as an emulsifier, likewise the chemical modifications that provide an amphiphilic character to said molecule; finally it find the conditions of elaboration of a Pickering emulsion.